Comparative Staging of Blastoderm Development at Oviposition in Eggs from Layer and Broiler Grandparent Breeder Flocks - Serdar Özlü (Turkish Journal of Agriculture: Food Science and Technology)
Recent decades were characterized by genetic selection of broiler and layer chickens for enhanced growth rate and meat yield or intensified egg production, respectively. It is to be expected that genetic selection for various traits would also influence embryo development. The effects of different strains of chickens on egg weight, stage of blastoderm, variation of the blastoderm development and Pearson correlation between egg weight and stage of blastoderm at oviposition were studied in the current study. Hatching eggs were randomly collected from three layer chicken lines (Layer-1, Layer-2, and Layer-3) raised in Poultry Research Institute, and two broiler grandparent flocks (Female and Male) from Aviagen Anadolu. The age of all chicken lines was 36 week. A total of 30 eggs in each line were used, and egg weight and the blastoderm development of the embryos were determined at oviposition time. At the end of the research, significant difference in egg weights (P0.05). The mean stage of blastoderm development in male grandparent line eggs significantly lower than other four genetic lines (P